Operational anomalies of the New Hungary Rural Development Program - Keszthelyi, Krisztián (Studia Mundi – Economica, 2019)
The aim of my paper is to highlight the effects of the rural development, particularly the mainrole of the subsidy system. The determining part of the agricultural and rural development isthe relevant effective subsidy systems. The study is focusing on the New Hungarian Rural Development Programme operating specialities and influence, which are my PhD study main components.